'I just don't trust my pelvic floor': Examining the bio-social barriers to maternal health and physical activity participation in a sample of mothers' from New Zealand - Marianne Clark; Holly Thorpe (Elsevier, 2023)
Maternal physical activity participation is associated with a range of positive mental and physical health outcomes. While a range of psycho-social and practical barriers to women's participation have been identified, little research has examined how these intersect with the physiological barriers posed by birthing injuries and the physical changes wrought by pregnancy and childbirth. In this study we address this gap using data collected through in-depth interviews with 20 women in Aotearoa New Zealand seeking to engage in regular exercise following childbirth. Guided by a socio-material conceptual framework, we examine women's physical activity engagement as bio-social phenomena. We pay particular attention to how women describe and navigate challenges posed by physiological considerations such as pelvic floor dysfunction, fatigue, the energetic demands of breastfeeding, and lingering birthing injuries. We argue these physical barriers are largely glossed over by policies, programmes and existing research that focus on motivating mothers to return to or become physically active. We suggest more sophisticated conceptual approaches are needed that explicitly acknowledge the overlapping biological and social dimensions of maternal physical activity in order to better support women through the complex postpartum period and beyond through enhanced resources, information, and general social awareness.